Happy is easy: the influence of affective states on cognitive control and metacognitive reports. Issue 6 (18th August 2021) - Culot, Catherine; Gevers, Wim
ABSTRACT: In many situations, engaging cognitive control is required to override automatic responses and to behave in an adaptive manner. However, cognitive control is also effortful and costly which makes it aversive. A fundamental question is how individuals decide to engage or not in cognitive control based on the costs of this effort and the motivation to achieve the goals. In the present study, we explored the hypothesis that affective states can influence this decision by changing participants' subjective experiences during the task. Participants performed a conflict task (arrow priming) and judged their feeling of difficulty after each trial. Affective states were induced by presenting emotional faces (happy, fearful or neutral) at the beginning of each trial. We found that participants subjectively judged happy trials as easier even though they objectively made more errors in this condition. Follow-up analyses revealed that participants engaged less cognitive control with happy than with neutral or fearful faces. We conclude that affective states influence the recruitment of cognitive control and associated metacognitive experiences.